2013
DOI: 10.1021/ef4016125
|View full text |Cite
|
Sign up to set email alerts
|

Morpholine-Induced Thermodynamic and Kinetic Inhibitions on Gas Hydrate Formation

Abstract: The unexpected formation of gas hydrates during production and transportation processes in petroleum industries is known as a serious problem. To deal with this problem, the oil and gas industry has been searching for hydrate inhibitors that have great performance and cost effectiveness. Recently, ionic liquids (ILs) have been suggested as novel hydrate inhibitors that are able to act in both thermodynamic and kinetic ways (so-called dual-function inhibitors). In this paper, we suggest a non-ionic liquid compo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…Generally, such additives are used to influence (inhibit or promote) gas hydrate formation depending on the application at hand, although the use of additives to promote gas hydrate dissociation has also been suggested. ,,, When discussing additives that influence gas hydrate formation, the mode of action is either thermodynamic (shifting the hydrate phase equilibrium conditions) and/or kinetic (altering the rate of hydrate nucleation and subsequent crystal growth). , Chemical additives that are used to inhibit gas hydrate formation are divided into two categories: thermodynamic hydrate inhibitors (THIs) and low-dosage hydrate inhibitors (LDHIs). , THIs such as methanol and ethylene glycol (EG) inhibit gas hydrate formation by interacting (forming hydrogen bonds) with the water molecules that make up the hydrate host lattice, thus shifting the hydrate phase equilibrium conditions to significantly harsher ones (higher pressures and lower temperatures). On the other hand, LDHIs are further subdivided into antiagglomerants (AAs) and kinetic hydrate inhibitors (KHIs). While the main function of AAs is to prevent formed hydrate nuclei from agglomerating and thus forming hydrate plugs (they do not affect hydrate nucleation), KHIs (e.g., PVP, PVCap) either delay hydrate nucleation or impede hydrate growth or both. ,,, With their ability to inhibit or delay hydrate formation, it is no surprise that the applicability of THIs and LDHIs is mostly limited to flow assurance, helping to reduce the uncertainty of operation as well as maintenance costs. Additionally, researchers have also proposed the idea of injecting chemical inhibitors (THIs) into deep marine settings so as to invoke instability in natural gas hydrate reservoirs and thus enable faster and more production of natural gas.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, such additives are used to influence (inhibit or promote) gas hydrate formation depending on the application at hand, although the use of additives to promote gas hydrate dissociation has also been suggested. ,,, When discussing additives that influence gas hydrate formation, the mode of action is either thermodynamic (shifting the hydrate phase equilibrium conditions) and/or kinetic (altering the rate of hydrate nucleation and subsequent crystal growth). , Chemical additives that are used to inhibit gas hydrate formation are divided into two categories: thermodynamic hydrate inhibitors (THIs) and low-dosage hydrate inhibitors (LDHIs). , THIs such as methanol and ethylene glycol (EG) inhibit gas hydrate formation by interacting (forming hydrogen bonds) with the water molecules that make up the hydrate host lattice, thus shifting the hydrate phase equilibrium conditions to significantly harsher ones (higher pressures and lower temperatures). On the other hand, LDHIs are further subdivided into antiagglomerants (AAs) and kinetic hydrate inhibitors (KHIs). While the main function of AAs is to prevent formed hydrate nuclei from agglomerating and thus forming hydrate plugs (they do not affect hydrate nucleation), KHIs (e.g., PVP, PVCap) either delay hydrate nucleation or impede hydrate growth or both. ,,, With their ability to inhibit or delay hydrate formation, it is no surprise that the applicability of THIs and LDHIs is mostly limited to flow assurance, helping to reduce the uncertainty of operation as well as maintenance costs. Additionally, researchers have also proposed the idea of injecting chemical inhibitors (THIs) into deep marine settings so as to invoke instability in natural gas hydrate reservoirs and thus enable faster and more production of natural gas.…”
Section: Introductionmentioning
confidence: 99%
“…While the main function of AAs is to prevent formed hydrate nuclei from agglomerating and thus forming hydrate plugs (they do not affect hydrate nucleation), 50−52 KHIs (e.g., PVP, PVCap) either delay hydrate nucleation or impede hydrate growth or both. [9][10][11][12][13]48,49,53 With their ability to inhibit or delay hydrate formation, it is no surprise that the applicability of THIs and LDHIs is mostly limited to flow assurance, helping to reduce the uncertainty of operation as well as maintenance costs. Additionally, researchers have also proposed the idea of injecting chemical inhibitors (THIs) into deep marine settings so as to invoke instability in natural gas hydrate reservoirs and thus enable faster and more production of natural gas.…”
Section: Introductionmentioning
confidence: 99%
“…Such affinity between KHIs and the formed hydrate particles prevents water molecules from approaching the formed hydrate (and allowing it to grow bigger) and significantly retards the blockage problem even under hydrate-forming conditions. There are also reports of a few ionic liquids that act as dual function inhibitors (playing both thermodynamic and kinetic inhibition roles) [14][15][16][17]. Basically, a dual function inhibitor is designed to improve inhibiting performance by playing two inhibition roles.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the stability of hydrate frameworks is influenced by guest molecules capable of hydrogen bonding with surrounding water molecules, such as alcohols, which are wellknown inhibitors of hydrate formation. 25,26 In this regard, the presence of strongly hydrogen bonding chemicals in the framework during hydrate formation may also disrupt hydrogen bonds among water molecules and would affect hydrate phase equilibria. As the first attempt, we measured three-phase (hydrate + aqueous liquid + vapor, HLV) equilibrium conditions of NH 4 F + CH 4 hydrates at various concentrations to investigate the thermodynamic stability in relation to a clathrate hydrate incorporated with NH 4 F. In addition, the formation kinetics of the NH 4 F + CH 4 hydrate was also investigated to evaluate the kinetic inhibition effect.…”
mentioning
confidence: 99%